Pengaruh Model PBL terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila Kelas VIII di SMP Negeri 24 Medan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the Problem Based Learning Model on the critical thinking skills of class VIII students at SMP Negeri 24 Medan in the 2024/2025 academic year. This experimental study used a quasi-experimental design with a nonequivalent control group design, involving experimental and control groups. The population of this study was all class VIII students of SMPN 24 Medan, with a sample of 2 classes, namely the experimental class and the control class. Data collection techniques include observation, pretest-posttest, and documentation. Data analysis used descriptive analysis, normality test, paired sample test, homogeneity, and independent sample t-test with SPSS Version 26. The results showed a significant increase in students' critical thinking skills in the experimental class after the implementation of the Problem Based Learning model, with an average value increasing from 58.25 to 82.25. Meanwhile, the control class only experienced a minimal increase, from 58.25 to 60.25. The results of the t-test also showed a significant difference between students' critical thinking skills before and after the Problem Based Learning model treatment. Based on the results of the study, it can be concluded that the Problem Based Learning learning model has a significant influence and effectiveness in improving the critical thinking skills of class VIII students of SMPN 24 Medan. Therefore, the Problem Based Learning model can be used as an alternative in improving students' critical thinking skills. Thus, this study is expected to contribute to the development of education at SMPN 24 Medan and other schools, and can be a reference for other teachers and researchers who want to develop similar research.